Significant career change to software development. A life-course perspective - Ana Maria, Preoteasa (Psihologia Resurselor Umane, 2021)
T The present study, based on qualitative data, investigates the significant career change through the life-course lens. Biographical interviews were conducted with people who changed their profession and the findings were characteristically reflective and subjective, foregrounding the participants’ interpretations of their layers of reality. Different type of resources: individual (Agency), community (Networking), and society (Labour market) were taken into account and the endeavour enabled to capture the triggers involved in career change process. The distinction between voluntary and involuntary career change decision helps to understand the reasons for which the change is chosen. There are major differences between those who leave involuntary their desired profession and those who discover that they have a calling for the software development. Moreover, the results advocate for the importance of early vocational counselling. On the other hand, evidence of discrimination encountered by new programmers could be addressed by HR departments in the IT organizations